Islam and International Relations - Edited By Proctor, J. Harris (New York Frederick A. Prager, 1965)
Scholarly papers on the influence of Islamic states on world affairs emanating from a symposium held at Duke University, June 10 to 13, 1963.
Keywords: Islam and world politics